2012
DOI: 10.1680/macr.11.00018
|View full text |Cite
|
Sign up to set email alerts
|

Flexural performance of reinforced recycled aggregate concrete beams

Abstract: The amount of concrete waste has increased significantly over the years due to reconstruction and the demolition of old buildings. Efforts have been made to utilise recycled aggregates to address some of the environmental problems associated with concrete waste and to promote the sustainability of concrete. A number of studies have been carried out to examine the mechanical properties, mixture design and structural performance of reinforced concrete (RC) beams comprising recycled aggregate. These studies repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 3 publications
2
32
0
Order By: Relevance
“…[3] and Eq. [4], the failure criterion for concrete under principal stresses state can be translated into that under combined compression and shear stresses state.…”
Section: A Failure Criterion For Rac Under Combined Compression and Smentioning
confidence: 99%
See 1 more Smart Citation
“…[3] and Eq. [4], the failure criterion for concrete under principal stresses state can be translated into that under combined compression and shear stresses state.…”
Section: A Failure Criterion For Rac Under Combined Compression and Smentioning
confidence: 99%
“…As a viable way to address demolition waste, recycled aggregate concrete (RAC) can help provide a sustainable construction material and has received considerable attention in many countries over the last several decades (1)(2). Although the recycling rate is high in some countries, the use of recycled aggregate is still confined to low-grade applications, such as pavement base, backfill for retaining and hard-core (3)(4)(5), which greatly limits the development and application of RAC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the structural behavior of RAC have been performed. The researches carried out on the beams showed that the flexural capacity of RAC beams were similar to that of the Natural Aggregate Concrete (NAC) beams [4][5][6]. The crack width of RAC beams was larger than that of NAC beams, while the flexural stiffness of RAC beams was lower compared with that of NAC beams.…”
Section: Introductionmentioning
confidence: 99%
“…The article by Park et al (2012) is also concerned with the seismic design of reinforced concrete. It considers the modelling of confined concrete under combined axial load and bending.The paper by Choi et al (2012) considers the flexural performance of reinforced concrete beams with recycled aggregate. Significantly, the performance of the beams with recycled aggregates is shown to be comparable with that of beams with natural aggregate.…”
mentioning
confidence: 99%
“…The paper by Choi et al (2012) considers the flexural performance of reinforced concrete beams with recycled aggregate. Significantly, the performance of the beams with recycled aggregates is shown to be comparable with that of beams with natural aggregate.…”
mentioning
confidence: 99%